COVID-19 AND FOOD PRICE: STUDY IN INDONESIA - Tuti Eka Asmarani (Riset Ekonomi Pembangunan, 2021)
This paper identified the long-run term relationship between COVID-19 and food prices in ten food commodities by using Autoregressive Distributed Lag (ARDL). Based on bound testing, the test statistics fall below the lower bound, the null hypothesis cannot be rejected. Therefore, there is no level the long-run relationship between COVID-19 and food prices, such as rice, chicken, chicken eggs, shallots, cayenne pepper, beef, garlic, red chilies, and cooking oil, and sugar. It means that crisis within crisis will not happen in Indonesia. The highest volatility in shallots, cayenne pepper, and red chilies occurred due to other factors, such as climate change and special moments.